MOTIVASI MEMEDIASI KEDISIPLINAN, KEMAMPUAN DAN LOYALITAS TERHADAP PRODUKTIVITAS KERJA KARYAWAN BAGIAN PRODUKSI PADA KOPERASI INDUSTRI BATUR JAYA CEPER - Devi Nurya Yuliyanti; Siti Maryam; Ida Aryati (JURNAL ILMIAH EDUNOMIKA, 2021)
The purpose of this study was to analyze the motivation to mediate discipline, ability and loyalty to the work productivity of production employees at the Batur Jaya Ceper Industrial Cooperative. The population of this study is 37 employees of the production division of the Batur Jaya Ceper Industrial Cooperative. The sample of this study used the census method, where all member Sof the population were sampled as many as 37 employees. This research is descriptive quantitative. This study uses validity, reliability and classic assumption tests. Hypothesis testing uses path analysis and sobel test. Data obtained from questionnaires from employees using a Likert scale to measure respondents' answers. This study was tested using SPSSS20 software. The results of this study indicate that the discipline variable mediated by motivation has an effectton work productivity. With a p-value of 0.00000392 00.05.TThe variable of loyalty mediated by motivation has an effect on work productivity. With p-value 0.03939366